BLOODSTREAM INFECTIONS IN FEBRILE NEUTROPENIC PATIENTS: BACTERIAL SPECTRUM AND ANTIMICROBIAL SUSCEPTIBILITY PATTERN - Butt, Tariq; Afzal, Raja Kamran; Ahmad, Rifat Nadeem; Salman, Muhammad; Mahmood, Abid; Anwar, Masood (Journal of Ayub Medical College Abbottabad, 2004)
Background: Bacterial infections are the major cause of morbidity and mortality among neutropenic patients. Prompt administration of empiric antimicrobial therapy for febrile neutropenic patients is considered vital. Before putting neutropenic patients on empiric antimicrobial regimens, it is essential to be aware of the spectrum of locally prevalent pathogens and their susceptibility pattern. Methods: We studied the bacterial spectrum and antimicrobial susceptibility pattern of organisms causing bloodstream infections in febrile neutropenic patients in Armed Forces Bone Marrow Transplant Centre, Rawalpindi and the Department of Oncology, Combined Military Hospital, Rawalpindi over a period of nine months from January to September 2002. Results: Blood specimens for culture and susceptibility testing were collected from 158 febrile patients with neutropenia. Eighty-three organisms were isolated from 60 patients. Thirty-six (43%) isolates were Gram-positive cocci and forty-seven (57%) were Gram-negative rods. Among the Gram-positive cocci, coagulase negative staphylococci (CoNS) were the predominant pathogens (26%), followed by Staphylococcus aureus (8%). Among Gram-negative rods, Escherichia coliwas the predominant isolate (13%) followed by Klebsiella pneumoniae (10%), Acinetobacter johnsonii (10%) and Pseudomonas aeruginosa (7%). Nine specimens yielded polymicrobial growth. Forty percent of Staphylococcus aureus and 55% of CoNS were resistant to methicillin. All the Gram-positive isolates were susceptible to vancomycin and teicoplanin. Among the Gram-negative rods, there was 100% resistance to ampicillin, 65% to gentamicin, 47% to amikacin and 66% to third generation cephalosporins. All the gram-negative isolates were susceptible to imipenem. Conclusion: The spectrum of isolates among febrile neutropenic patients in our population appears to be shifting towards Gram-positive microorganisms. Due to increasing levels of drug resistance among the isolates, a glycopeptide in combination with a carbapenem would be a prudent choice as empiric therapy in high-risk cases. Keywords: Neutropenia; infection; fever; empiric therapy; Pakistan.